The blueness index, investment choice, and portfolio allocation - Muhammad Zubair Mumtaz; Zachary A. Smith (Asian Development Bank Institute (ADBI), 2021)
Recently, the concept of "blue finance" was introduced to the world. Blue finance envisages that ocean firms issue financial instruments to obtain funds and take necessary measures to make the ocean environment blue. To measure the blueness of a firm, we estimate the blueness index using GHG emissions as a percentage of sales. This study proposes a theoretical model to estimate the portfolio's utility function by incorporating the blueness factor. The result suggests a positive relationship between the blueness proxy and optimal investment allocation. In the absence of blueness, their returns would be taxed; thus, the participation of investment in blue bonds decreases. Last, we examine the factors that cause stock returns and document a positive association between the blueness of a firm and stock returns. This evidence indicates that firms that are relatively 'bluer' may be more perceptive of the public's preference for sustainable investments, thereby leading them to outperform
Keywords: G11; G12; H21; 330; ocean emissions; blueness index; bonds; portfolio allocation; emission tax